Nitrendipine and Dementia: Forgotten Positive Facts? - Novotny, Michal; Klimova, Blanka; Valis, Martin (Frontiers in Aging Neuroscience, 2018)
Nowadays, there are about 50 million people suffering from dementia worldwide. In 2030, it is expected that there will be 82 million people living with dementia and in 2050, their number should reach 152 million. This increase in the number of people with dementia results in significant social and economic problems. Therefore, researchers attempt to reduce risk factors causing the development of dementia such as high blood pressure. Epidemiological studies have shown that hypertension increases the risk of dementia at an older age. It can, therefore, be assumed that hypertension therapy will reduce the risk of dementia. However, previous clinical studies have shown that the efficacy of different antihypertensive drugs differs in this respect. The drug group that appears to be the most effective in these analyses is calcium channel blockers (CCBs). The most significant preventive efficacy in terms of protection against dementia has been demonstrated with nitrendipine. Its use is, therefore, particularly advantageous in elderly patients with systolic hypertension who are at high risk of dementia. The purpose of this study is to restore the discussion on the prevention of vascular dementia and Alzheimer’s dementia with nitrendipine in indicated hypertonic patients. The authors performed a literature search of available sources describing the issue of dementia, hypertension and its treatment with nitrendipine. In addition, they made a comparison and evaluation of relevant findings. The results of the detected research studies indicate that nitrendipine is able to reduce the incidence of dementia [Alzheimer’s disease (AD), vascular and mixed] by 55%. The treatment of 1,000 patients with nitrendipine for 5 years may prevent 20 cases of dementia. However, what has not yet been explained is the temporal link between hypertension and dementia due to the long-time intervals between hypertension and the development of dementia.